Follow-Up of Adefovir Dipivoxil Induced Osteomalacia: Clinical Characteristics and Genetic Predictors - Zhao, Jiao; Feng, Wei-guang; Wei, Zhe; Zhou, Jian; Chen, Xiao-yun; Zhang, Zhen-lin (Frontiers in Pharmacology, 2021)
Adefovir dipivoxil (ADV) is widely used for chronic hepatitis B therapy in China. To explore the clinical features and prognosis of ADV-induced osteomalacia and to analyze the association between osteomalacia and genetic variants in 51 drug transporters genes. Clinical and follow-up data of the ADV-treated patients were collected. Target capture sequencing was used to identify genetic variations of 51 drug transporter genes. A total of 193 hepatitis B patients treated with ADV were enrolled, of whom 140 had osteomalacia. The other 53 without osteomalacia were included in the control group. The median duration of ADV treatment before the onset of osteomalacia was 6.5 years (range:1.5-7 years). We found that most patients with osteomalacia had hypophosphatemia, high serum alkaline phosphatase levels, hypouricemia, nondiabetic glycosuria, proteinuria. Stopping ADV administration, supplementing calcitriol and calcium were effective treatments. During 3-6 months of follow-up, the clinical symptoms and biochemical indicators of patients with osteomalacia have been significantly improved. There was no significant difference in duration of adefovir treatment in patients with or without osteomalacia (p = 0.791). Through regression analysis, we found that age was a risk factor for osteomalacia [per 1 year, odds ratio (OR), 1.053; 95% confidence interval (95% CI), 1.020-1.087; p = 0.015]. 1992 single nucleotide variants were found using target capture sequencing. However, the associations of genetic variants of 51 drug transporter genes and the risk of osteomalacia were negligible. Osteomalacia is prone to occur in patients with chronic hepatitis B treated with long-term ADV at a therapeutic dose. After standard treatment, the prognosis is mostly good. We failed to find genetic variants that can predict the risk of ADV-induced osteomalacia.